Enhancement of storage life and maintenance of quality in tomato fruits by preharvest salicylic acid treatment - Baninaiem, Elham; Dastjerdi, Abdolmajid Mirzaalian (Frontiers in Sustainable Food Systems, 2023)
Tomato fruits are usually characterized by a short postharvest life. Their quality decreases during storage due to losses in nutritional quality and decay. Salicylic acid (SA) has an important role in plant development and response to environmental stress. This research aimed at evaluating the effects of preharvest salicylic acid application on extending the storage life, and ripening of tomatoes (Solanum lycopersicum cv. Baraka). As a hybrid seed, the “Baraka” cultivar is appropriate for subtropical regions. Three consecutive weeks before harvest, foliar spraying with SA was applied at different concentrations (1, 2, and 4 mM). After storage for 10, 20, 30, and 40 days at 10°C with 85–95% relative humidity (RH), the tomatoes had decreased levels of a* value (redness), decay, electrolyte leakage, and chilling injury after being treated with salicylic acid. In comparison to the control, these characteristics were linked to increased levels of firmness, titratable acidity, ascorbic acid, and ascorbate peroxidase activity. According to the findings, fruit quality was best maintained at 4 mM SA, whereas it was least effective at 1 mM SA. Overall, the results showed that, SA can be considered a potent treatment that can effectively control postharvest loss.